Ability Cognitive Children Age Early Between Methods Brain Gym and Methods Providing Duty - Anisa Nurwasilatus; Dinita Vita Apriloka (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2021)
Children's cognitive abilities have not been appropriately achieved. This is due to the use of methods that are considered less effective in the learning process. The purpose of this study was to determine the reality of differences in cognitive abilities of early childhood with the Brain Gym method and the assignment method for Group B at RA Al-Wafi Panyileukan Bandung City. The research method used is Quasi Experiment with non-equivalent control group design research. The results showed that children's cognitive abilities using the Brain Gym method and those using the Giving Task method had significant differences. This was evidenced by the results of hypothesis testing, which showed the t value = 8.97 more effective than the t table value = 2.043 at a significance level of 5 %.